2014
DOI: 10.3747/co.21.2125
|View full text |Cite
|
Sign up to set email alerts
|

Using pet-ct to Reduce Futile Thoracotomy Rates in Non-Small-Cell Lung Cancer: A Population-Based Review

Abstract: with pet-ct positive N1 status and with tumours larger than 3 cm even with a pet-ct negative mediastinum. KEY WORDSNon-small-cell lung cancer, positron-emission tomography-computed tomography, thoracotomy, lymphatic metastasis or pathology, mediastinal staging, endobronchial ultrasonography, mediastinoscopy, endoscopic ultrasonography

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…However, both of these methods can be impacted by relatively subtle changes in scope pressure and method of image acquisition. Of the 75 patients recruited, 9 (12%) had N2 disease found at surgery which is lower than other published data . A 12% futile thoracotomy rate as highlighted by the authors is not perfect, but would overall be deemed acceptable as it reflects the fact that the role of the MDT is to give patients the benefit of the doubt for surgery where doubt exists.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…However, both of these methods can be impacted by relatively subtle changes in scope pressure and method of image acquisition. Of the 75 patients recruited, 9 (12%) had N2 disease found at surgery which is lower than other published data . A 12% futile thoracotomy rate as highlighted by the authors is not perfect, but would overall be deemed acceptable as it reflects the fact that the role of the MDT is to give patients the benefit of the doubt for surgery where doubt exists.…”
mentioning
confidence: 71%
“…Of the 75 patients recruited, 9 (12%) had N2 disease found at surgery which is lower than other published data. 13 A 12% futile thoracotomy rate as highlighted by the authors is not perfect, but would overall be deemed acceptable as it reflects the fact that the role of the MDT is to give patients the benefit of the doubt for surgery where doubt exists. This reflects best practice guidelines.…”
mentioning
confidence: 97%
“…Although PET-CT has reduced the number of futile thoracotomies, its sensitivity and specificity range from 75% to 95% for detecting metastatic disease. 22 Various studies have shown the stage of the disease correlates with survival, but in cases of equivocal disease due to either small lesions or a tumor with low metabolism, for example, bronchoalveolar carcinoma, 23 abnormal blood markers such as elevated plasma fibrinogen may serve as an adjunct to indicate a more advanced stage. Similarly, in patients with borderline fitness for curative resection, abnormal blood markers may be a useful marker of poor outcome and help in making the decision to proceed with either surgery or radical radio/chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging plays an essential role in the clinical or cTNM classification, with CT being the method of choice, given its wide availability [ 12 ]. In addition, 18 F-FDG PET/CT has become another standard tool in pre-treatment assessment, with advantages over conventional techniques, for staging both the mediastinum [ 13 , 14 ], as well as extrathoracic disease [ 15 ] having demonstrated it lowers the number of useless thoracotomies, and improves cost-effectiveness in the management of these patients [ 16 ]. Therefore, given the importance of an integrated morphological-functional assessment for proper treatment planning, one technique without the other is not understandable.…”
Section: To Define the Applications Of Functional And Molecular Imagimentioning
confidence: 99%